METODE TAFSIR AHKAM SAIF AL-DIN AL-AMIDI DALAM PENYELESAIAN KASUS ‘IDDAH DAN IḤDĀD PADA MASYARAKAT MODERN - Habib Maulana Maslahul Adi (At-Ta'aruf : Jurnal Hukum Keluarga Islam, 2024)
The discourse on 'iddah and 'iḥdād is still an interesting topic for discussion, both by academics, activists, and lay people. In fact, it is not uncommon for female influencers and activists who do not actually have a deep understanding of fiqh discourse to also comment on this matter. Therefore, it is appropriate for this discourse to return to refer to Ushul Fiqh experts, such as Saif al-Din al-Amidi. This research aims to reveal the resolution of 'iddah and iḥdād cases in modern society from the perspective of the kitab Al-Iḥkām fī Uṣūl al-Aḥkām by Al-Amidi, along with the methodology of its legal interpretation. The results of this research show that 'iddah is still mandatory for women who are separated from their husbands either due to divorce or death, even though there is technological sophistication that is able to ensure that the uterus is empty of the fetus. Regarding limitations (iḥdād) such as leaving the house and putting on make-up can be tolerated as long as these things are urgent to do and are directly related to the needs of life and those of their family.